BIVALVE RESOURCES IN THE COASTAL WATERS OF BINH THUAN PROVINCE (VIET NAM) AND THEIR RELATIONSHIP WITH THE STRONG UPWELLING - Tuan, Vo Si; Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2009)
Based on analysis of the published papers and data obtained by different projects  implemented  during  1990  -  2005,  it  is highlighted  that  the  coastal  waters  of  Binh Thuan Province (South Viet Nam) are characterised by the abundant distribution of sublitoral bivalves, including inter alia: Chlamys nobilis, Anadara antiquata, Modiolus philippinarum, Paphia undulata and Pinna sp. The richness of nutrients provided by the strong upwelling and its  direct  ecological  effect  -  abundance  of  phytoplankton  (and possible  material transformation following strong upwelling) are considered as favourable factors for growth and high biomass of these bivalves. Levels of the relation with ecological effects of the strong upwelling change among species due to differences on population ecology of the species. The Scallop  C.  nobilis  depends  on  the  strong  upwelling  at  the  highest  level  and  seconded by mussel M. philippinarum. The clams A. antiquata and P.  undulata are influenced by factors caused by upwelling and river discharge. It is able to wrap up that changes in position and intensity  of  the strong  upwelling  would  control  biological  processes  and  as  a result, fluctuation  of  population  biomass  of  these  species  in  the  coastal  waters  of  Binh  Thuan province.